Development of Ice Cream Formula from Katuk Leaf Juice ( Sauropus androgynous ) and Pineapple Juice ( Ananas Comosus L. merr ) as a Source of Flavonoid and Additional Vitamin C for Breastfeeding Mother - nike satriana; Ice Yolanda Puri; Jeallyza Muthia Azra (Stikes Syedza Saintika Padang, 2026)
WHO estimates that of the 46.28 million newborns in 2020, 32.8% received sufficient breast milk, while 12% did not receive any breast milk at all. This problem is caused by the mother's breast milk being low or not flowing smoothly. Flavonoids are components of lactagongum containing flavonoids that can increase breast milk production which plays a role in the hormones prolactin and oxytocin. Plants containing flavonoids include katuk leaves. Katuk leaves are also known as vegetables that stimulate breast milk among the community. This study aims to develop an ice cream formulation with the addition of katuk leaf juice and pineapple juice as a source of flavonoids and additional vitamin C for breastfeeding mothers. The sample is ice cream with the addition of katuk leaf juice and pineapple juice with a ratio of each treatment, namely (F0 0:0, F1 30:20, F2 35:15, F3 40:10). The samples were subjected to hedonic tests and proximate nutrient content tests (using the gravimetric, Kjeldahl, Soxhlet, and different methods), iron content tests using the SNI 01-2896-1998 method, descriptive sensory tests of selected products using the consensus method, and flavonoid and vitamin C tests using spectrophotometry and titrimetry methods. The results obtained were the selected formula, F3, with the highest proximate nutrient content and meeting the SNI ice cream quality requirements. Descriptive sensory results included aroma and taste parameter analysis, where the resulting descriptors were aroma (like leaf, milky, and unpleasant) and taste (sweet, milky, and bitter). The flavonoid content of the selected product was 0.02% and Vitamin C content was 1.25%. Ice cream with the addition of katuk leaf juice and pineapple juice, which contain flavonoids and vitamin C, can be used as a food source of flavonoids and additional vitamin C for breastfeeding mothers.